UV-B Pre-treatment Alters Phenolics Response to Monilinia fructicola Infection in a Structure-Dependent Way in Peach Skin - Santin, Marco; Neugart, Susanne; Castagna, Antonella; Barilari, Martina; Sarrocco, Sabrina; Vannacci, Giovanni; Schreiner, Monika; Ranieri, Annamaria (Frontiers in Plant Science, 2018)
Phenolic compounds represent a large class of secondary metabolites, involved in multiple functions not only in plant life cycle, but also in fruit during post-harvest. phenolics play a key role in the response to biotic and abiotic stresses, thus their accumulation is regulated by the presence of environmental stimuli. The present work aimed to investigate how different pre-UV-B-exposures can modulate the phenolic response of peach fruit infected with Monilinia fructicola. Through HPLC-DAD-MSn, several procyanidins, phenolic acids, flavonols and anthocyanins were detected. Both UV-B radiation and fungal infection were able to stimulate the accumulation of phenolics, dependent on the chemical structure. Regarding UV-B exposure, inoculated with sterile water, 3 h of UV-B radiation highest concentration of phenolics was found, especially flavonols and cyanidin-3-glucoside far from the wound. However, wounding decreased the phenolics in the region nearby. When peaches were pre-treated with 1 h of UV-B radiation, the fungus had an additive effect in phenolic accumulation far from the infection, while it had a subtractive effect with 3 h of UV-B radiation, especially for flavonols. Canonical discriminant analysis and Pearson correlation revealed that all phenolic compounds, except procyanidin dimer, were highly regulated by UV-B radiation, with particularly strong correlation for quercetin and kaempferol glycosides, while phenolics correlated with the fungus infection were quercetin-3-galactoside, quercetin-3-glucoside, kaempferol-3-galactoside and isorhamnetin-3-glucoside. Modulation of pathogen-induced phenolics also far from inoculation site might suggest a migration of signalling molecules from the infected area to healthy tissues.